2022
DOI: 10.1155/2022/7205692
|View full text |Cite
|
Sign up to set email alerts
|

Caries-Preventive Effect and Retention of Glass-Ionomer and Resin-Based Sealants: A Randomized Clinical Comparative Evaluation

Abstract: Background. Deep fissures are highly unprotected from the development of caries. Resin-based materials and glass-ionomer cements for sealing fissures are useful in caries control through physical barrier formation, which prohibits metabolic exchange between fissure microorganisms. Retention is one of the most critical properties of fissure sealants. This in vivo study is aimed at comparing and evaluating the clinical efficacy of resin and glass ionomer-based fissure sealants on first permanent molars with foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Across all KQs, 3 systematic reviews (total of 20 684 participants) of 54 unique trials (53 publications) and 23 additional studies (in 27 publications; total of 15 026 participants) were included (Figure 3). One study assessed diagnostic accuracy of screening; the systematic reviews and other 22 studies (19 randomized clinical trials and 3 nonrandomized trials) addressed preventive interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all KQs, 3 systematic reviews (total of 20 684 participants) of 54 unique trials (53 publications) and 23 additional studies (in 27 publications; total of 15 026 participants) were included (Figure 3). One study assessed diagnostic accuracy of screening; the systematic reviews and other 22 studies (19 randomized clinical trials and 3 nonrandomized trials) addressed preventive interventions.…”
Section: Resultsmentioning
confidence: 99%
“…66,72 In 1 of the trials, outcomes were very similar when sealants were administered by a dentist or a schoolteacher. Two subsequent, fair-quality trials 84,85 (n = 187 and n = 50) also reported inconsistent findings for glass ionomer sealants vs no sealants (eTables 16 and 17 in the Supplement).…”
Section: Sealantsmentioning
confidence: 99%
“…In in vivo and in vitro studies, the contamination of the sur-face enamel with saliva was shown to be the most significant factor that affected both the retention and the clinical success of the resin-based fissure sealants [39].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the caries incidence of different dental sealants. With the results of the studies that have blank control groups, we summarize the preventive fractions are 92% for both resin sealant and glass ionomer sealant at a 6-month follow-up ( 52 ); 64% - 88% for resin sealant, and 88% for glass ionomer sealant at an 18-month follow-up ( 68 ); 61% for resin sealant and 35% for glass ionomer at a 60-month follow-up ( 56 ). Results of hybrid sealant were limited in the literature.…”
Section: Effects Of Dental Sealant In Preventing and Arresting Caries...mentioning
confidence: 99%
“…Table 1 shows the retention rates of dental sealants published in the past ten years (2012–2022). For resin sealant, the retention rate ranges from 11% to 89% at a 6-month follow-up ( 40 , 52 , 61 , 62 ); from 18 to 88% at a 12-month follow-up ( 26 , 45 , 47 , 49 51 , 55 , 58 – 60 , 65 , 67 ); from 24% to 70% at an 18-month follow-up ( 54 , 57 , 68 ); from 21% to 80% at a 24-month follow-up ( 44 , 46 , 48 , 63 , 64 , 66 ). Studies with longer follow-up periods were limited.…”
Section: Longevity Of Dental Sealantmentioning
confidence: 99%